Comparative analysis of processing speed impairments in TLE, FLE, and GGE: Theoretical insights and clinical Implications - Adam Falah; Gavin P. Winston (Epilepsy & Behavior Reports)
In this narrative review, we explore the differences in processing speed (PS) impairments among three epilepsy conditions; Temporal Lobe Epilepsy (TLE), Frontal Lobe Epilepsy (FLE) and Genetic Generalized Epilepsy (GGE) with a focus on Juvenile Myoclonic Epilepsy (JME). Despite the large body of research focusing on cognition in epilepsy, the intricacies of PS impairments in the epilepsy syndromes have not been fully explored. We investigate the cognitive profiles with focus on PS associated with each of the three conditions, and the neuropsychological methods employed. Furthermore, we evaluate PS in epilepsy within the theoretical frameworks of PS, such as the Relative Consequence Model, the Limited Time Mechanism Model, and the Neural Noise Hypothesis. We find the main challenge of PS research in epilepsy is the inconsistency of assessment methods utilized in different studies. Furthermore, PS impairments are not isolated but rather interconnected to other cognitive domains. Thus, future studies need to standardize PS assessment tools, and incorporate innovative solutions such as technology and neuroimaging techniques to further enhance our understanding of PS impairments in epilepsy.